In Vitro Herb Drug Pharmacokinetic Interaction Study of 5 Fluorouracil (5-FU) with Turmacin - Satapathy, Trilochan; Yadav, Rajni; Roy, Amit (Journal of Neonatal Surgery, 2025)
Background: Herbal supplements are frequently used with anticancer chemotherapy, prompting worries over clinically significant herb–drug interactions. Turmacin®, a polysaccharide-rich aqueous extract of Curcuma longa, exhibits mucilage-forming, immunomodulatory, and antioxidant characteristics that may affect medication absorption and metabolism. 5-Fluorouracil (5-FU), a hydrophilic chemotherapy drug characterized by limited and variable absorption, is notably influenced by herbal components. Objective: The objective of this study is to examine the in-vitro pharmacokinetic interaction between Turmacin and 5-FU by various mechanistic models, encompassing phytochemical profiling, physicochemical analysis, Caco-2 permeability, and P-glycoprotein (P-gp) ATPaseassays. Methods: The standardized Turmacin extract was analyzed for its phytochemical and physicochemical properties. Caco-2 monolayers were employed to assess bidirectional permeability (AP→BL and BL→AP) of 5-FU, with or without Turmacin (200 µg/mL). Transporter interaction was evaluated utilizing human P-glycoprotein membrane vesicles using ATPase activity experiments. Physicochemical and phytochemical profiling encompassed assessments of acid value, ash content, melting point, soluble extractives, and the detection of flavonoids, tannins, alkaloids, essential oils, and antioxidants. Results: Turmacin markedly diminished the AP→BL permeability of 5-FU by approximately 32%, while augmenting BL→AP efflux and raising the efflux ratio by around 41%, signifying improved P-gp–mediated transport. The ATPase assay indicated reduced inorganic phosphate release in the presence of Turmacin, implying partial inhibition of ATP hydrolysis and alteration of P-gp functionality. Phytochemical screening verified the existence of many beneficial compounds, whilst physicochemical examination demonstrated elevated purity, thermal stability, and hydrophilicity. In summary, diminished absorptive transport, augmented efflux, and heightened microsomal degradation all signify impaired availability of 5-FU in the presence of Turmacin Conclusion: Turmacin significantly modifies the in-vitro pharmacokinetic properties of 5-FU by diminishing intestinal permeability, regulating efflux transporter activity, and increasing metabolic breakdown. These findings underscore a notable herb–drug interaction that may diminish the systemic absorption of 5-FU. Patients are urged to exercise caution when taking turmeric-based supplements during 5-FU treatment, and additional in-vivo studies are necessary to confirm these findings